2020
DOI: 10.1186/s40359-020-0376-y
|View full text |Cite
|
Sign up to set email alerts
|

The value of hope: development and validation of a contextual measure of hope among people living with HIV in urban Tanzania a mixed methods exploratory sequential study

Abstract: Background: Hope or hopefulness enhances coping and improves quality of life in persons with chronic or incurable illnesses. Lack of hope is associated with depression and anxiety, which impact negatively on quality of life. In Tanzania, where HIV prevalence is high, the rates of depression and anxiety are over four times higher among people living with HIV (PLH) compared to persons not infected and contribute annual mortality among PLH. Tanzania has a shortage of human resources for mental health, limiting ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 73 publications
1
10
0
1
Order By: Relevance
“…This study has found that adolescents with low hope were 9 times likely to have depression and 3.8 times likely to have suicidal ideations. This nding is similar to studies done SSA among PLWH showed that feeling of hopelessness predisposed an individual to mental disorders such as depression, anxiety and suicidality (29,31). The tool used to assess hope is new and a study to set the cutoff points on the hope scale used for this population is of paramount importance, as it has not yet been done.…”
Section: Discussionsupporting
confidence: 82%
“…This study has found that adolescents with low hope were 9 times likely to have depression and 3.8 times likely to have suicidal ideations. This nding is similar to studies done SSA among PLWH showed that feeling of hopelessness predisposed an individual to mental disorders such as depression, anxiety and suicidality (29,31). The tool used to assess hope is new and a study to set the cutoff points on the hope scale used for this population is of paramount importance, as it has not yet been done.…”
Section: Discussionsupporting
confidence: 82%
“…In turn, this ongoing contact coupled with heavy workloads and limited resources can negatively impact the well-being as well as the effectiveness of the HS providers. Such challenges are also noted in the academic literature and are important to consider in HS programming and planning (Jones, 2000;Siril et. al., 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Viver com esperança, pelas PVHIV, auxilia no enfrentamento da infecção e favorece viver de uma maneira mais intensa, mesmo diante das dificuldades impostas pelo curso da doença e do tratamento. 31 De fato, a esperança tem sido apontada como um fator de interferĂȘncia na qualidade de vida de PVHIV. 32,33 Ter um bom relacionamento familiar esteve associado Ă  sensação de felicidade.…”
Section: Discussionunclassified